Modified fiber filter cloth and application thereof in heavy metal ion adsorption
By etching dicyandiamide on the surface of polyester fibers and bridging it with arginine, the polyphenol hydroxyl adsorption layer is formed by loading tannin to form a polyphenol hydroxyl adsorption layer, which solves the problem of low removal efficiency of heavy metal ions in textile wastewater and achieves an efficient and environmentally friendly heavy metal adsorption effect.
Patent Information
- Application Number
- CN202411602081.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Existing textile wastewater treatment technology is difficult to efficiently remove heavy metal ions, especially polyester fiber filter cloth, which has limited adsorption capacity and cannot meet the needs of large-scale treatment.
By etching the surface of the polyester fiber by dicyandiamide and using arginine as a bridge agent, the tannic acid is loaded on the fiber surface to form a stable polyphenol hydroxyl adsorption layer, and its heavy metal ion adsorption ability is improved.
It significantly improves the adsorption performance of polyester fiber filter cloth to heavy metal ions, especially the efficient removal effect of Cu2+ and Zn2+ plasma, providing an efficient and environmentally friendly textile wastewater treatment solution.
Smart Images

Figure CN119553495A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of environmental pollution control and functional materials, in particular to textile wastewater treatment, and specifically to a modified fiber filter cloth and its application in heavy metal ion adsorption. Background Art
[0002] The textile industry generates a large amount of wastewater during the production process, which contains a variety of pollutants, especially heavy metal ions (such as copper, chromium, nickel, etc.). These heavy metal ions are difficult to degrade and have bioaccumulation. After entering the water body, they can be transmitted through the food chain, posing a serious threat to the ecological environment and human health. If the heavy metal-contaminated textile wastewater is not effectively treated, it will cause long-term harm to water resources and the environment. Therefore, the development of efficient technology for removing heavy metal ions has become an important issue in textile wastewater treatment.
[0003] At present, common methods for removing heavy metal ions include chemical precipitation, ion exchange, membrane separation and adsorption. Among them, adsorption is widely used in heavy metal wastewater treatment due to its advantages such as high efficiency, low cost and simple operation. Although traditional adsorption materials such as activated carbon and natural minerals have certain adsorption capacity, their adsorption capacity is often limited and cannot meet the needs of large-scale treatment. Therefore, the development of efficient functional adsorption materials has become a research hotspot.
[0004] The fiber disc filter is a high-efficiency, low-energy solid-liquid separation equipment, which is widely used in the treatment of municipal sewage, industrial wastewater and reclaimed water reuse. Its main function is to intercept suspended particles, colloids and some soluble pollutants in the water through high-precision fiber filter cloth, thereby achieving deep purification. The equipment uses fiber filter cloth as the filter medium and relies on the rotation and backwashing technology of the filter disc to ensure the continuity and efficiency of filtration. Compared with traditional heavy metal removal methods such as chemical precipitation, ion exchange and activated carbon adsorption, the fiber disc filter has the following advantages: compact equipment structure, small footprint, high treatment efficiency, simple operation and maintenance, and low energy consumption.
[0005] As a core component, polyester fiber disc filter cloth is mainly used to remove suspended solids, sediment, microorganisms and some organic pollutants in water. However, although polyester fiber has excellent mechanical properties, such as high strength and wear resistance, as well as good chemical stability, and can withstand acids, alkalis and a variety of chemicals, its surface chemical activity is low. This leads to limited adsorption capacity of polyester fiber for heavy metal ions, especially when directly treating wastewater containing heavy metals, the removal effect may be insufficient. In order to improve the adsorption performance of polyester fiber, surface modification is usually required, such as introducing functional groups or compounding with highly adsorbent materials to give it stronger heavy metal capture ability, thereby expanding its application range and further improving the sewage treatment effect. Polyphenol compounds, especially tannic acid (TA), because of the multiple phenolic hydroxyl groups in its molecules, can form stable chelates with heavy metal ions and become an ideal adsorbent. TA effectively removes metal ions from water by coordinating with heavy metal ions. Studies have shown that TA has a strong adsorption capacity for a variety of heavy metal ions (such as Cu2+, Zn2+, Pb 2 +) have good chelating effect. Therefore, the modified material based on TA has a significant effect in removing heavy metal ions in textile wastewater, and has the advantages of being green, environmentally friendly and easy to obtain. The prior art has a method of directly immersing nanofibers in an aqueous solution of TA for modification, but the tannic acid loading and adhesion stability of the modified fibers prepared by this method are not very ideal and need to be further improved. Summary of the invention
[0006] The present invention aims to improve the heavy metal ion adsorption capacity of polyester fiber filter cloth by modifying it with tannic acid (TA), so as to provide an efficient and environmentally friendly solution for textile wastewater treatment.
[0007] The present invention is achieved through the following technical solutions:
[0008] The first object of the present invention is to provide a modified fiber filter cloth, comprising polyester fiber and tannic acid loaded on the surface of the polyester fiber; the polyester fiber is pre-etched with dicyandiamide; the tannic acid is loaded on the surface of the polyester fiber with an arginine bridging agent.
[0009] In one embodiment of the present invention, surface etching using dicyandiamide comprises the following steps:
[0010] The polyester fiber is placed in a 2-5% dicyandiamide solution, with NaOH as a catalyst, and treated in a water bath at 60-100° C. for 10-30 minutes.
[0011] In one embodiment of the present invention, loading tannic acid on the surface of polyester fiber comprises the following steps:
[0012] S01, immersing the surface-etched polyester fiber in an arginine solution, shaking and treating it under alkaline conditions for 2 to 4 hours, taking it out after the treatment, washing it and drying it to obtain arginine-treated polyester fiber;
[0013] S02, immersing the polyester fiber treated with arginine in a tannic acid solution, oscillating the solution under acidic conditions for 1 to 8 hours, taking out the fiber after treatment, washing it and drying it to obtain the polyester fiber loaded with tannic acid.
[0014] In one embodiment of the present invention, the concentration of the arginine solution is 4-6 mg / ml.
[0015] In one embodiment of the present invention, the concentration of the tannic acid solution is 2-4 mg / ml.
[0016] The second object of the present invention is to provide a method for preparing the modified fiber filter cloth, comprising the following steps:
[0017] S1. Place the polyester fiber in a 2-5% dicyandiamide solution, use NaOH as a catalyst, and treat it in a water bath at 60-100° C. for 10-30 minutes;
[0018] S2, immersing the polyester fiber after surface etching in an arginine solution, shaking it under alkaline conditions, taking it out after treatment, washing it and drying it to obtain arginine-treated polyester fiber;
[0019] S3, immersing the polyester fiber treated with arginine in a tannic acid solution, shaking the solution under acidic conditions, taking out the fiber after treatment, washing it and drying it to obtain the modified fiber filter cloth.
[0020] In one embodiment of the present invention, the concentration of the arginine solution is 4-6 mg / ml.
[0021] In one embodiment of the present invention, the treatment time in step S2 is 2 to 4 hours.
[0022] In one embodiment of the present invention, the concentration of the tannic acid solution is 2-4 mg / ml.
[0023] In one embodiment of the present invention, the treatment time in step S3 is 1 to 8 hours.
[0024] In one embodiment of the present invention, the processing time in step S3 is 1 to 2 hours.
[0025] The third object of the present invention is to provide application of the modified fiber filter cloth in sewage treatment.
[0026] The fourth object of the present invention is to provide application of the modified fiber filter cloth in heavy metal ion adsorption.
[0027] Beneficial effects of the present invention:
[0028] The present invention can effectively improve the surface activity of polyester fiber by etching the surface of polyester fiber with dicyandiamide. The amino group in dicyandiamide can react with the surface of polyester fiber, destroy part of the molecular structure of the fiber, form a porous structure, and thus increase the specific surface area. This etching enables the surface of polyester fiber to have more adsorption sites, providing a good foundation for subsequent functional modification. Under the etching effect of dicyandiamide, a variety of active groups are formed on the surface of polyester fiber, which provides attachment sites for subsequent TA loading, thereby improving the adsorption performance of heavy metal ions.
[0029] In order to further improve the loading amount and binding firmness of tannic acid on the surface of polyester fiber, the present invention adopts arginine (L-Arginine) as a bridging agent. Arginine contains guanidine and carboxyl groups in its molecular structure, which can bind to the surface of the etched polyester fiber through hydrogen bonds or electrostatic effects, and simultaneously react with the phenolic hydroxyl groups in the tannic acid molecules to enhance its adhesion stability. The introduction of arginine not only increases the loading amount of tannic acid, but also provides additional adsorption sites, significantly improving the heavy metal ion removal efficiency of the adsorbent material.
[0030] Through the etching of dicyandiamide and the bridging effect of arginine, a stable polyphenolic hydroxyl adsorption layer is formed on the surface of polyester fiber, which effectively improves its chelating ability for heavy metal ions, making the modified polyester fiber show excellent adsorption performance in treating heavy metal ions in textile wastewater, especially for Cu2+, Zn2+ and other ions in textile wastewater. This modification method provides a new solution for efficient and environmentally friendly textile wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 It is a modification mechanism diagram of the polyester filter cloth of the present invention.
[0033] Figure 2 This is a graph showing the change in water contact angle of the polyester filter cloth before and after modification of the present invention.
[0034] Figure 3 It is the time variation of the loading of TA of the present invention on PET, PET / APTES, PET / PEI and PET / L-Arg.
[0035] Figure 4 The absorbance curve change of TA released from the PET / TA and PET / L-Arg / TA nanofiber pads of the present invention at 292 nm in deionized water is
[0036] Figure 5 The polyester filter cloth Cu of the present invention 2+ Adsorption related experiments.
[0037] Figure 6 The XPS elemental spectra of the polyester filter cloth before and after modification and the changes in group bond energy before and after adsorption are shown.
[0038] Figure 7 The polyester filter cloth before and after modification of the present invention is 2+ Schematic diagram of the selective adsorption.
[0039] Figure 8 It is the recycling performance of the polyester filter cloth of the present invention. DETAILED DESCRIPTION
[0040] The present invention is further described below in conjunction with specific examples. These implementation cases are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the claims attached to the application.
[0041] Source of raw materials
[0042] The technical solution of the present invention is described in detail below in conjunction with specific embodiments. In the following embodiments, unless otherwise specified, the reagents, materials and equipment used can be purchased from commercial sources, or prepared by conventional methods, or are commonly used in the industry.
[0043] Example 1
[0044] A high-precision commercial plush filter cloth of model WL-102 was selected as the substrate. The filter cloth was made of polyester and the length of the plush was 25 mm. The pretreatment process was completed in a 2% dicyandiamide solution with NaOH as a catalyst and treated in a water bath at 80°C for 20 minutes.
[0045] The pre-treated polyester filter cloth (size 2cm×2cm×1cm) was placed in an arginine (5mg / ml) solution, the pH value of which was adjusted to 9.0 by 0.1M HCl / NaOH. After oscillating in a constant temperature oscillator at 25°C and 100rpm for 2 hours, the sample was taken out, rinsed with deionized water 3 times, and dried for 12 hours to obtain a sample of PET / L-Arg.
[0046] The obtained PET / L-Arg was immersed in a TA solution (2 mg / ml), the pH value of the solution was adjusted to 4.0 by 0.1 M HCl / NaOH, and the solution was oscillated in a water bath at 25°C and 120 rpm for 0.5, 1, 1.5, and 2 hours, respectively. The sample was taken out and rinsed repeatedly with deionized water for 3 times, and then dried for 12 hours to finally obtain PET / L-Arg / TA.
[0047] Example 2
[0048] A high-precision commercial plush filter cloth of model WL-102 was selected as the substrate. The filter cloth was made of polyester and the length of the plush was 25 mm. The pretreatment process was completed in a 5% dicyandiamide solution with NaOH as a catalyst and treated in a water bath at 80°C for 20 minutes.
[0049] The pre-treated polyester filter cloth (2 cm × 2 cm × 1 cm) was placed in an arginine (5 mg / ml) solution, the pH of which was adjusted to 9.0 by 0.1 M HCl / NaOH. After oscillating in a constant temperature oscillator at 25°C and 100 rpm for 3 hours, the sample was taken out, rinsed with deionized water 3 times, and dried for 12 hours to obtain a sample of PET / L-Arg.
[0050] The obtained PET / L-Arg was immersed in a TA solution (2 mg / ml), the pH value of the solution was adjusted to 4.0 by 0.1 M HCl / NaOH, and the solution was shaken in a water bath at 25°C and 120 rpm for 4 hours. The sample was taken out and rinsed repeatedly with deionized water for 3 times, and then dried for 12 hours to finally obtain PET / L-Arg / TA.
[0051] Example 3
[0052] A high-precision commercial plush filter cloth of model WL-102 was selected as the substrate. The filter cloth was made of polyester and the length of the plush was 25 mm. The pretreatment process was completed in a 5% dicyandiamide solution with NaOH as a catalyst and treated in a water bath at 80°C for 20 minutes.
[0053] The pre-treated polyester filter cloth (size 2cm×2cm×1cm) was placed in an arginine (5mg / ml) solution, the pH value of which was adjusted to 9.0 by 0.1M HCl / NaOH. After oscillating in a constant temperature oscillator at 25°C and 100rpm for 2 hours, the sample was taken out, rinsed with deionized water 3 times, and dried for 12 hours to obtain a sample of PET / L-Arg.
[0054] The obtained PET / L-Arg was immersed in a TA solution (4 mg / ml), the pH value of the solution was adjusted to 4.0 by 0.1 M HCl / NaOH, and the solution was shaken in a water bath at 25°C and 120 rpm for 5 hours. The sample was taken out and rinsed repeatedly with deionized water for 3 times, and then dried for 12 hours to finally obtain PET / L-Arg / TA.
[0055] Comparative Example 1
[0056] A high-precision commercial plush filter cloth of model WL-102 was selected as the substrate. The filter cloth was made of polyester and the length of the plush was 25 mm. The pretreatment process was completed in a 2% dicyandiamide solution with NaOH as a catalyst and treated in a water bath at 80°C for 20 minutes.
[0057] The pre-treated polyester filter cloth (size 2cm×2cm×1cm) was placed in an aminopropyltriethoxysilane (APTES, 5mg / ml) solution, and the pH value of the solution was adjusted to 9.0 by 0.1M HCl / NaOH. After oscillating in a constant temperature oscillator at 25°C and 100rpm for 2 hours, the sample was taken out, rinsed with deionized water 3 times, and dried for 12 hours to obtain a sample of PET / APTES.
[0058] The obtained PET / APTES was immersed in a TA solution (2 mg / ml), the pH value of the solution was adjusted to 4.0 by 0.1 M HCl / NaOH, and the solution was oscillated in a water bath at 25°C and 120 rpm for 0.5, 1, 1.5, and 2 hours, respectively. The sample was taken out and rinsed repeatedly with deionized water for 3 times, and then dried for 12 hours to finally obtain PET / APTES / TA.
[0059] Comparative Example 2
[0060] A high-precision commercial plush filter cloth of model WL-102 was selected as the substrate. The filter cloth was made of polyester and the length of the plush was 25 mm. The pretreatment process was completed in a 2% dicyandiamide solution with NaOH as a catalyst and treated in a water bath at 80°C for 20 minutes.
[0061] The pre-treated polyester filter cloth (size 2cm×2cm×1cm) was placed in a polyethyleneimine (PEI, 5mg / ml) solution, and the pH value of the solution was adjusted to 9.0 by 0.1M HCl / NaOH. After oscillating in a constant temperature oscillator at 25°C and 100rpm for 3 hours, the sample was taken out, rinsed with deionized water 3 times, and dried for 12 hours to obtain a sample PET / PEI.
[0062] The obtained PET / PEI was immersed in a TA solution (2 mg / ml), the pH value of the solution was adjusted to 4.0 by 0.1 M HCl / NaOH, and oscillated in a water bath at 25°C and 120 rpm for 0.5, 1, 1.5, and 2 hours, respectively. The sample was taken out and rinsed repeatedly with deionized water for 3 times, and then dried for 12 hours to finally obtain PET / PEI / TA.
[0063] Comparative Example 3
[0064] A high-precision commercial plush filter cloth of model WL-102 was selected as the substrate. The filter cloth was made of polyester and the length of the plush was 25 mm. The pretreatment process was completed in a 2% dicyandiamide solution with NaOH as a catalyst and treated in a water bath at 80°C for 20 minutes.
[0065] PET was immersed in a TA solution (2 mg / ml), the pH value of the solution was adjusted to 4.0 by 0.1 M HCl / NaOH, and the solution was oscillated in a water bath at 25°C and 120 rpm for 0.5, 1, 1.5, and 2 hours, respectively. The sample was taken out and rinsed repeatedly with deionized water for 3 times, and then dried for 12 hours to finally obtain PET / TA.
[0066] Results and Testing
[0067] The performance of the samples was checked by the following tests.
[0068] Fabric hydrophilicity test: Hydrophilicity is an important indicator for evaluating the performance of fabrics. This experiment uses the POWER2000 large platform contact angle meter to measure the water contact angle of fabrics. Cut the dry fabric into thin strips and fix it on the experimental clamp. At room temperature, drop a drop of deionized water on the surface of the fabric sample on the shooting table, take a photo, record the data after the contact angle stabilizes, and analyze it.
[0069] The change of water contact angle of polyester filter cloth before and after modification is shown in the figure Figure 2 As shown, it can be seen that after loading L-Arg, the contact angle rapidly decreases to 50.1° due to the hydrophilicity of L-Arg. With the deposition of TA and the formation of the polyphenol coating, the contact angle decreases to a minimum of 39.3° after 1 hour. Beyond this deposition time, a thick coating forms on the surface, resulting in a gradual loss of the fiber structure. Therefore, the water contact angle increases due to the decrease in surface roughness, where the effect of the reduced roughness outweighs the increased hydrophilicity of the coating.
[0070] In order to verify the role of the bridging agent in enhancing the loading of TA on PET, we used UV spectrophotometry to measure the absorbance of the impregnation solution and calculate the loading capacity of TA. Figure 3The temporal variation of TA loading on PET, PET / APTES, PET / PEI, and PET / L-Arg was described. The results showed that L-Arg as a bridging agent significantly increased the loading capacity of TA, with a 70% increase in total TA loading, compared with no bridging agent, bridging agent APTES, and bridging agent PEI. This enhancement is due to the rich functional groups of L-Arg, which promote hydrogen bonding and other non-covalent interactions with the ester groups in PET and the phenolic hydroxyl groups in TA, thereby increasing the loading capacity of TA and having important implications for subsequent heavy metal adsorption experiments.
[0071] In order to evaluate the desorption performance of TA, 0.1 g of PET / TA1 and PET / L-Arg / TA n The nanofibers were immersed in 30 mL of deionized water (pH = 5). The temperature was controlled by a refrigerated circulator. At appropriate time intervals, the release medium was removed and the same volume of fresh medium at the same temperature was added. The concentration of TA in the release medium was determined by UV / visible spectroscopy at a wavelength of 292 nm. Figure 4 It showed that TA was released in all samples. However, after adding L-Arg, PET / L-Arg / TA n The TA release of the samples was significantly reduced. L-Arg interacts with tannic acid through its amine and carboxyl functional groups through non-covalent interactions, such as hydrogen bonding, electrostatic interactions, and π-π stacking, which helps to fix the tannins more firmly on PET and reduce its tendency to decompose in water. The amine and carboxyl functional groups of L-Arg interact with TA through non-covalent interactions, which fix the tannins more firmly on PET and reduce its tendency to decompose in water. The release of TA gradually increased with the increase of the thickness of the double-layer membrane, indicating that L-Arg enhances the stability of TA in water through strong non-covalent interactions and improves the recovery performance of the adsorbent.
[0072] XPS elemental analysis: The XPS test of PET / L-Arg / TA before and after the adsorption of copper ions was performed using an X-ray photoelectron spectrometer model ESCALAB 250Xi from Thermo Scientific, USA. A monochromatic aluminum X-ray source (1486.6eV) and a fixed retarding mode were used. Charge correction was performed using the C1s binding energy of 284.8eV as the standard. The surface element content was determined by the peak area ratio after correction with the experimentally determined sensitivity factor. The XPS elemental spectra of the polyester filter cloth before and after modification and the changes in the group bond energy before and after adsorption are shown in Figure 2. Figure 6 As shown, it can be seen that after adsorption, Cu 2p signals appear in the full XPS spectrum, which is favorable for Cu 2+ Has been successfully adsorbed on the adsorbent ( Figure 6 In addition, the state of copper is mainly Cu2+ exists in the form of Figure 6 As shown in b. Cu 2+ After adsorption, the CO / COC and CO peaks of O 1s shifted to 532.81 and 531.21 eV ( Figure 6 c), further indicating that oxygen-containing functional groups are involved in the adsorption process. In addition, due to the interaction between N atoms and Cu 2+ After sharing electrons, the electron density decreases, and the peaks of -CONH- and -NH2 shift to higher binding energies ( Figure 6 (d)
[0073] The concentration of heavy metal ions in the solution was measured by atomic adsorption spectrometer (AA-240, Varian, USA).
[0074] Adsorption performance measurement: In order to study Cu 2+ In order to investigate the adsorption behavior of PET, PET / L-Arg and PET / L-Arg / TA fabrics, we conducted the following adsorption experiments. In general, 40 mL of copper sulfate (CuSO4-5H2O, Macklin) solution (Cu 2+ The concentration was 40-120 mg / L) and adsorbed at room temperature for 12 hours. The adsorbent was then collected and the Cu content in the filtrate was determined by atomic absorption spectrophotometer. 2+ The concentration of Cu on the adsorbent 2+ The adsorption amount was calculated according to the following formula.
[0075]
[0076]
[0077] Where, C0 (mg / L) is the initial Cu 2+ Concentration, C e (mg / L) is the equilibrium concentration after adsorption. t (mg / L) is the Cu content in the solution 2+ Real-time concentration. e (mg / g) and q t (mg / g) respectively Cu 2+ The equilibrium adsorption capacity and real-time adsorption capacity of the adsorbent. M (g) is the amount of adsorbent, and V (L) is the volume of the solution.
[0078] The effect of pH (2.0-6.0) on the adsorption performance was evaluated by conducting adsorption experiments in a thermostatic shaker at 30°C, 120 rpm, and 12 h. The pH of the solution was adjusted with HCL (37%, Macklin) and NaOH (Macklin). 2+The adsorption capacity was tested at a concentration of 100 mg / L. The kinetic adsorption experiment was carried out at a pH of 5.0, a temperature of 30°C, and a Cu 2+ The concentration was 40-120 mg / L.
[0079] The pH value of aqueous solution plays an important role in the adsorption of heavy metal ions because it may affect the surface functional groups of the adsorbent and the solution chemical properties of the pollutants. Therefore, we first investigated the effect of solution pH on the adsorption of Cu by PET / L-Arg / TA1. 2+ The effect of adsorption capacity, such as Figure 5 As shown in a. PET / L-Arg / TA1 for Cu 2+ The adsorption amount (qe) of MgCl2 increases with the increase of pH from 2 to 6, and the maximum adsorption amount is 77.3 mg / g at pH = 6. This phenomenon is similar to that observed in the literature before. Amine and -OH groups are easily protonated in strong acidic solutions, thus inhibiting the binding with CuCl2. 2+ As the solution H + With the decrease of concentration, the existing amine and -OH groups are favorable for Cu 2+ Therefore, pH is positively correlated with the adsorption amount. However, when the solution pH is greater than 5, Cu 2+ Cu(OH)2 precipitate was generated. Therefore, the pH of the solution was set to 5 in subsequent adsorption studies.
[0080] In order to evaluate the effect of polyester filter cloth on Cu 2+ The adsorption performance of ions was studied for PET, PET / L-Arg and PET / L-Arg / TA n Tested. Figure 5 b is the Cu 2+ Comparison of adsorption performance. The adsorption capacity of PET is relatively low, at 21.4 mg / g, indicating that PET without chemical modification has a poor adsorption capacity for Cu 2+ The adsorption amount of PET / L-Arg / TA1 was 77.5 mg / g, which was higher than 42.1 mg / g of PET / L-Arg. This indicates that the L-Arg bridging strategy enhances the adsorption of Cu 2+ Moreover, qe increased as the TA deposition time was extended from 0.5 h to 1 h. This is because TA made the fiber surface coarser, introduced more adsorption sites, and improved the overall adsorption capacity. However, when the deposition time exceeded 1 h, the surface structure of the adsorbent was transformed into a coating film, resulting in a decrease in active sites and, thus, a decrease in adsorption capacity.
[0081] In order to study the PET / L-Arg / TA1 2+ The adsorption kinetics at different concentrations were studied, and the adsorption behavior, such as Figure 5As shown in c. Adsorption of Cu 2+ The amount of Cu increased rapidly at the beginning. Then the increasing trend weakened and finally stabilized. This was due to the decrease in the number of effective binding sites. Therefore, 4h was finally selected as the Cu 2+ The optimal time for adsorption experiment was investigated. 2+ The effect of concentration on adsorption capacity. Figure 5 As shown in Figure d, the adsorption capacity shows such a trend that the initial concentration of copper ions has a significant effect on the adsorption capacity. At low concentrations (40 mg / L), there are fewer available ions, resulting in a decrease in adsorption capacity. As the concentration increases (60-80 mg / L), the more adsorption sites are occupied, the greater the adsorption capacity. At high concentrations (100-120 mg / L), the adsorption sites are saturated and the adsorption amount reaches a maximum value (68.5 mg / g). This relationship highlights the importance of initial concentration in optimizing the adsorption of heavy metal ions.
[0082] In order to investigate the adsorption selectivity, a multicomponent mixture (Cu 2+ 、Zn 2+ and Pb 2+ ) in the competitive adsorption. The adsorbent was immersed in 40 mL of mixed metal ion solution and adsorbed at 25 ° C for 6 hours. The results are shown in Figure 7 As shown in the figure, it can be seen that the adsorption of these three ions by PET is very low, which is due to the lack of functional groups on the adsorbent surface that can chelate with heavy metal ions. 2+ It exhibits high adsorption selectivity for Cu 2+ The adsorption capacity of Zn 2+ (23.3mg / g) and Pb 2+ (16.9 mg / g) is 2.5-3.8 times the adsorption capacity. This selectivity may be related to the hydrated ion radius of the metal ions. Ions with smaller hydrated radii, such as Cu 2+ , it is easier to diffuse through the pores of the nanofiber membrane. This ease of diffusion often leads to faster adsorption rate and higher adsorption capacity.
[0083] The reusability of PET / L-Arg / TA1 was tested. The recovered PET / L-Arg / TA1 was treated with EDTA solution (0.01 mol / L, 50 mL) for 2 h to remove the adsorbed Cu 2+ After washing with deionized water and drying, the regenerated PET / L-Arg / TA1 was used for the next adsorption run. Figure 8As shown in the figure, the results of 5 recovery tests show that the first adsorption amount is 70.3 mg / g, and the fifth adsorption amount drops to about 66.7 mg / g). The results show that the functional groups of PET / L-Arg / TA1 do not detach significantly during the desorption process, and the adsorption capacity is well maintained. 2+ It has high adsorption performance and good regeneration stability.
[0084] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A modified fiber filter cloth, characterized in that: The invention comprises polyester fiber and tannic acid loaded on the surface of the polyester fiber; the surface of the polyester fiber is etched by dicyandiamide in advance; and the tannic acid is loaded on the surface of the polyester fiber by an arginine bridge agent.
2. The modified fiber filter cloth according to claim 1, characterized in that: Surface etching using dicyandiamide includes the following steps: The polyester fiber is placed in a 2-5% dicyandiamide solution, with NaOH as a catalyst, and treated in a water bath at 60-100° C. for 10-30 minutes.
3. The modified fiber filter cloth according to claim 1, characterized in that: Loading tannic acid on the surface of polyester fiber includes the following steps: S01, immersing the surface-etched polyester fiber in an arginine solution, shaking and treating it under alkaline conditions for 2 to 4 hours, taking it out after the treatment, washing it and drying it to obtain arginine-treated polyester fiber; S02, immersing the polyester fiber treated with arginine in a tannic acid solution, oscillating the solution under acidic conditions for 1 to 8 hours, taking out the fiber after treatment, washing it and drying it to obtain the polyester fiber loaded with tannic acid.
4. The method for preparing the modified fiber filter cloth according to any one of claims 1 to 3, characterized in that: The steps include: S1. Place the polyester fiber in a 2-5% dicyandiamide solution, use NaOH as a catalyst, and treat it in a water bath at 60-100° C. for 10-30 minutes; S2, immersing the polyester fiber after surface etching in an arginine solution, shaking it under alkaline conditions, taking it out after treatment, washing it and drying it to obtain arginine-treated polyester fiber; S3, immersing the polyester fiber treated with arginine in a tannic acid solution, shaking the solution under acidic conditions, taking out the fiber after treatment, washing it and drying it to obtain the modified fiber filter cloth.
5. The preparation method according to claim 4, characterized in that: The concentration of the arginine solution is 4-6 mg / ml.
6. The preparation method according to claim 4, characterized in that: The processing time in step S2 is 2 to 4 hours.
7. The preparation method according to claim 4, characterized in that: The concentration of the tannic acid solution is 2-4 mg / ml.
8. The preparation method according to claim 4, characterized in that: The processing time in step S3 is 1 to 8 hours.
9. Use of the modified fiber filter cloth according to any one of claims 1 to 3 in sewage treatment.
10. Use of the modified fiber filter cloth according to any one of claims 1 to 3 in the adsorption of heavy metal ions.
Citation Information
Patent Citations
Method of modifying sorbents based on cellulose
RU2791803C1
Cited By
Forestry waste-based modified adsorbent as well as preparation method and application thereof
CN120827856A